2001
DOI: 10.1177/001440290106700209
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural Aspects of Parent Involvement in Transition Planning

Abstract: This study surveyed 308 African-American, Hispanic-American, Native-American and European-American parents to assess their level of participation in various transition planning activities and how important each activity was to them. In addition, 52 school professionals completed a parallel survey of their perceptions toward parent participation. Analyses indicate that culturally and linguistically diverse parents are active in the transition process and, in some instances, their level of reported participation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 24 publications
4
95
0
1
Order By: Relevance
“…Of the six articles, two used quantitative methods (Geenen, Powers, & Lopez-Vasquez, 2001; Hasnain & Balcazar, 2009), one used qualitative (Goff, Martin, & Thomas, 2007), and the other three used mixed methods (Geenen et al, 2003;Landmark, Zhang, & Montoya, 2007;Leake, Burgstahler, & Izzo, 2011). None of the six articles involved the investigation of a specific intervention designed to improve transition outcomes; rather, they were focused on describing or defining current practice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the six articles, two used quantitative methods (Geenen, Powers, & Lopez-Vasquez, 2001; Hasnain & Balcazar, 2009), one used qualitative (Goff, Martin, & Thomas, 2007), and the other three used mixed methods (Geenen et al, 2003;Landmark, Zhang, & Montoya, 2007;Leake, Burgstahler, & Izzo, 2011). None of the six articles involved the investigation of a specific intervention designed to improve transition outcomes; rather, they were focused on describing or defining current practice.…”
Section: Resultsmentioning
confidence: 99%
“…None of the six articles involved the investigation of a specific intervention designed to improve transition outcomes; rather, they were focused on describing or defining current practice. Two studies included youth with disabilities as participants, seeking their perspectives about factors that impact their transition goals and outcomes (Goff et al, 2007;Leake et al, 2011), while three studies included parents and/or special educators as participants (Geenen et al, 2001(Geenen et al, , 2003Landmark et al, 2007). The sixth study was a secondary analysis of data collected from the NHIS-D longitudinal study to determine predictors of community-based versus facility-based employment outcomes for individuals with disabilities (Hasnain & Balcazar, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Ivey (2004) claimed that home and school misunderstandings were commonly reported by parents of children with AS, and Hay and Winn (2003) emphasised communication and collaboration difficulties as exacerbating these misunderstandings. Geenen, Powers, and Lopez-Vasquez (2001) identified that parents' stress levels were exacerbated by adversarial relationships with professionals. Ivey (2004) also argued that parent and student perceptions were often missing from the literature.…”
mentioning
confidence: 99%